The Impact of Inter-Generational Relationships on Depressive Symptoms in Elderly Parents in Rural Jammu, India - Richa Mahajan; Hemaal Koul; Rajiv K Gupta; Riya Gupta; Bhavna Langer; Rashmi Kumari; Tasvinder Kour; Nahida Chowdhary (National Journal of Community Medicine)
Background: Given the paucity of literature in the Jammu region on intergenerational relationships that contribute to a connected society promoting empathy and family support, this study was undertaken to evaluate its effect on depressive symptoms in older parents. The aim of this study was to examine patterns of intergenerational relationships between aging parents and their adult children.